What does the Internet tell us about green spaces? The virtual communication about three Budapest public park projects and its potential in green infrastructure protection - Szabó, Patrícia; Sárospataki, Máté (4D Journal of Landscape Architecture and Garden Art, 2024)
The study explores the online communication regarding three Budapest public parks opened in 2022, investigating what type of information is available about them to a wide audience and how vital ecological processes and living park elements are represented. Applying the methodof content analysis, the selected texts from primary (online platforms related to client, designer, or contractor) and secondary (interviews with designers, professionalpraises) sources were coded. The ten main code groups give an overview of the major fields and components of green space development projects. Each field appears in a different degree of importance, but the proportion of Design aspectscodes is similar for the three projects. Sustainability is mentioned in all three, suggesting that it is a key factor in the positive public perception of the project. However, the depth with which this is discussed varies, being merely an empty token in certain contexts. In the case of one project, there was regular communication about the project implementation on behalf of the creators. This is the same project that gives the most detailed information about living park elements and the ecological processes taking place between them. It is concluded that the conscious and responsible online communication about public green space projects has the potential to raise awareness by increasing the knowledge about and visibility of the essential ecosystem services provided by parks and green infrastructure in general, thereby contributing to their long-term protection.
Keywords: open space development; content analysis; communication; climate change adaptation; visibility